Ventricular remodeling and diastolic myocardial dysfunction in rats submitted to protein-calorie malnutrition - Fioretto, JR; Querioz, S. S.; Padovani, Carlos Roberto [UNESP]; Matsubara, Luiz Shiguero [UNESP]; Okoshi, Katashi [UNESP]; Matsubara, Beatriz Bojikian [UNESP] (Amer Physiological Soc, 2002)
The effects of protein-calorie malnutrition (PCM) on heart structure and function are not completely understood. We studied heart morphometric, functional, and biochemical characteristics in undernourished young Wistar rats. They were submitted to PCM from birth (undernourished group, UG). After 10 wk, left ventricle function was studied using a Langendorff preparation. The results were compared with age-matched rats fed ad libitum (control group, CG). The UG rats achieved 47% of the body weight and 44% of the left ventricular weight (LVW) of the CG. LVW-to-ventricular volume ratio was smaller and myocardial hydroxyproline concentration was higher in the UG. Left ventricular systolic function was not affected by the PCM protocol. The myocardial stiffness constant was greater in the UG, whereas the end-diastolic pressure-volume relationship was not altered. In conclusion, the heart is not spared from the adverse effects of PCM. There is a geometric alteration in the left ventricle with preserved ventricular compliance despite the increased passive myocardial stiffness. The systolic function is preserved.
Keywords: left ventricular function; Langendorff preparation; isolated heart